DESIGNING INSTRUCTIONAL MATERIALS FOR BLENDED LEARNING BY USING SCHOOLOGY FOR SPEAKING CLASS OF ENGLISH EDUCATION STUDY PROGRAM OF TEACHER TRAINING AND EDUCATION FACULTY OF BANDAR LAMPUNG UNIVERSITY - Margaretha Audrey S.C.; Dameria Magdalena Sidabalok (Bandar Lampung University (UBL), 2016)
This study aims to make instructional materials for blended learning suitable for implementation in Speaking class. The blended learning will combine face to face method with LMS-Schoology as the media for web-based learning. The participants of this research are the second semester of English Education Study Program in UBL who took speaking 2 subjects. The result of the research showed that the instructional materials for blended learning method in speaking 2 classes are able to facilitate students learning process and increase their activeness in learning.